Investigation of the cardiovascular system of schoolchildren aged 13-14 years - Iryna Kuzmenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine the level of functioning of the cardiovascular system of schoolchildren of the 8th-9th grades. Material & Methods: 59 schoolchildren of 8-9 grades took part in the study. Such methods of research as theoretical analysis and generalization of scientific and methodological literature, methods of studying the functional state of the cardiovascular system and methods of mathematical statistics were applied. Results: a comparison of the parameters of the cardiovascular system in the sexual, age aspects and with the corresponding scoring scale is presented. Conclusion: in the sexual aspect, it was found that the indicators of the functioning of the cardiovascular system in schoolchildren of the 8th grade are higher in girls, and in schoolchildren of the 9th grade in young men; with age, in men, there are somewhat larger values of indicators, in girls, on the contrary, less; comparison with the scoring scale showed that the results of schoolchildren of 8-9 grades correspond to the "average" level.